2016
DOI: 10.1007/s10460-016-9719-y
|View full text |Cite
|
Sign up to set email alerts
|

What would farmers do? Adaptation intentions under a Corn Belt climate change scenario

Abstract: This paper examines farmer intentions to adapt to global climate change by analyzing responses to a climate change scenario presented in a survey given to largescale farmers (n = 4778) across the US Corn Belt in 2012. Adaptive strategies are evaluated in the context of decision making and farmers' intention to increase their use of three production practices promoted across the Corn Belt: no-till farming, cover crops, and tile drainage. This paper also provides a novel conceptual framework that bridges a typol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 56 publications
1
51
1
Order By: Relevance
“…O'Connor argues that in a perpetual search for greater profits, capitalism does 1 Studies of the impact of no-till use on N loss in various forms have been inconsistent, and therefore, the benefits of no till specific to N management as an adaptive practice are still considered unknown (Robertson et al, 2013) or largely dependent on integrating no till with a suite of practices (Daryanto, Wang, & Jacinthe, 2017). 2 As one exception, Roesch-McNally, Arbuckle, and Tyndall (2017) find that some farmers are dealing with weather variability and extremes by using increased tillage, which would increase carbon dioxide emissions. Their analysis and discussion generally focus on farmers using conservation management practices though.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Connor argues that in a perpetual search for greater profits, capitalism does 1 Studies of the impact of no-till use on N loss in various forms have been inconsistent, and therefore, the benefits of no till specific to N management as an adaptive practice are still considered unknown (Robertson et al, 2013) or largely dependent on integrating no till with a suite of practices (Daryanto, Wang, & Jacinthe, 2017). 2 As one exception, Roesch-McNally, Arbuckle, and Tyndall (2017) find that some farmers are dealing with weather variability and extremes by using increased tillage, which would increase carbon dioxide emissions. Their analysis and discussion generally focus on farmers using conservation management practices though.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…As this discussion suggests, it is possible that farmers are responding to the impacts of climate change, specifically heavy rain events, in ways that increase GHG emissions from agriculture. Despite the significance of this potential feedback loop, little empirical work has explored if farmers use quick fix adaptation practices, if they use increased N rates to mitigate weather‐related risks (Arbuckle & Rosman, ), and overall, we currently know little about whether farmers are implementing practices in response to climate risks (Mase, Gramig, & Prokopy, ) as the majority of the literature on adaptation practice adoption has examined behavioural intentions or supportive attitudes toward conservation adaptive practices (e.g., Arbuckle, Morton, & Hobbs, ; Arbuckle, Prokopy, et al, ; Roesch‐McNally et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To the contrary, research has revealed a diversity of farmer identities [13,[26][27][28]. Some are oriented toward maximizing economic benefits, which is associated with lower levels of adoption of environmental measures, but not all farmers fit this mold [8,16,29]. This leads to the importance of social identity, which has been linked to support for certain practices, including in some cases environmental or mitigative measures [7,30].…”
Section: Climate Change and Farmer Behaviourmentioning
confidence: 99%
“…There is a need for the research and extension community to continue developing strategies for effective collaboration and communication with stakeholders, who have diverse needs and expertise (Moser and Ekstrom, 2010;Akerlof et al, 2012;Wibeck, 2014;AgCC, 2016). Existing literature suggests effective mechanisms for researchers to engage with agricultural decisionmakers, and for building the necessary extension capacityincluding that of conservation district staff, private-sector technical service providers, and others-to deliver actionable climate change information (McNie, 2012;Kirchhoff et al, 2013;Wibeck, 2014;Prokopy et al, 2015a;Roesch-McNally et al, 2017). In order to produce relevant tools and research, scientists need to be well-versed in the concerns and challenges that regional producers are facing and how those producers make decisions (McNie, 2012;Kirchhoff et al, 2013;Weaver et al, 2013;Allen et al, 2017).…”
Section: Partnerships and Communication Among Researchers And Decisiomentioning
confidence: 99%
“…For some climate changerelated risks (e.g., water shortages, flooding), effective responses may be required beyond the farm level. There is a need to ensure that-at a minimum-management and policy decisions implemented in the near term do not undermine farmers' ability to cope with more severe climate change impacts in the future Roesch-McNally et al, 2017).…”
Section: Priorities For Partnerships and Communication Among Researchmentioning
confidence: 99%